Analysis of user experience during interaction with automotive repair workshop websites - Radosław Danielkiewicz; Mariusz Dzieńkowski (Journal of Computer Sciences Institute)
The study presented here focuses on analyzing and comparing the user experience of two automotive repair workshop website search engines. The research tools used were usability tests, user interviews and eye tracking. These were aimed at assessing the functionality, intuitiveness and overall user experience when using the analyzed sites. The results show that users encountered a variety of problems with navigation and search functions, and made suggestions for improving and expanding the website functions. Nevertheless, despite some differences in the evaluations of specific aspects of both services, there was little difference in the effectiveness of the set scenarios.